Kesesuaian Kebutuhan Ruang Terbuka Hijau Berdasarkan Proporsi RTH Wilayah Perkotaan Di Kabupaten Mojokerto - Kharisma Kadri, Mohtana (LPPM ITK, 2023)
The role of green open space in urban areas is very important to reduce the saturation of urban communities. In addition to ecological functions, green open spaces are also important for the community to carry out socio-cultural, aesthetic, and economic interactions. Therefore, the government stipulates by law that each city must set aside 30% of its area for green open space (RTH) in its regional plans. Mojokerto has changed its function from year to year, such as agricultural land, which has changed its designation into residential areas, buildings, and industrial areas, as well as roads. In order to prevent uncontrolled land use change and a lack of attention to green open space in the future, it is necessary to carry out an analysis of land requirements in the Green Open Space (RTH) area in the Mojokerto region.